2014
DOI: 10.1016/s2095-3119(13)60692-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorination on Soil Chemical Properties and Nitrogen Uptake for Tomato Drip Irrigated with Secondary Sewage Effluent

Abstract: Chlorination is usually an economical method for treating clogging in drip emitters during sewage application. Appropriate assessment of the responses of soil and crop is essential for determining an optimal chlorination scheme. During 2008 to 2009, field experiments were conducted in a solar-heated greenhouse for tomato drip irrigated with secondary sewage effluent, to investigate the influences of chlorine injection intervals and levels on soil chemical properties and nitrogen uptake. Injection intervals ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Further studies should be conducted considering the characteristics of reclaimed water more comprehensively. In addition, the effects of the practices for clogging treatment of the irrigation system, such as chlorination and acid injection, on the soil chemical properties and nitrogen uptake of crops are also of great interest for reclaimed water irrigation (Li and Li, ; Li et al ., ).…”
Section: Management Of Reclaimed Water Irrigationmentioning
confidence: 97%
“…Further studies should be conducted considering the characteristics of reclaimed water more comprehensively. In addition, the effects of the practices for clogging treatment of the irrigation system, such as chlorination and acid injection, on the soil chemical properties and nitrogen uptake of crops are also of great interest for reclaimed water irrigation (Li and Li, ; Li et al ., ).…”
Section: Management Of Reclaimed Water Irrigationmentioning
confidence: 97%
“…Compared with GW irrigation, SW irrigation increased plant N uptake by 7% in 2014 and 9% in 2015, on average (Table ). This indicates that the nutrient‐rich SW could contribute to elevating the crop N uptake and therefore become a highly attractive alternative for farmers (Singh et al , ; Li et al , ; Marofi et al , ). Field experiments on Bermuda grass pasture (da Fonseca et al , ) found that irrigation with secondary‐treated sewage effluent increased the dry matter and crude protein content of the above‐ground grass relative to potable water irrigation.…”
Section: Resultsmentioning
confidence: 99%
“…It activates various enzymes involved in the metabolism of plants. Studies have shown that in soils that receive TWW for irrigation, the availability of total N, K, and available P increase considerably [52][53][54][55][56]. Similarly, Abd-Elwahed [57] and Xu et al [58] observed increased total N, available K, and P contents in the top layer of soil for irrigated plants with wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the use of TWW for irrigation improves soil fertility and the chemical and physical properties of soil [44][45][46], and can provide soils with OM and nutrients (N, P, K, Ca, Mg, B, Zn, Cu, Mn, etc. ), thus improving crop production [17,47,54,55,59,61,62]. Wang et al [74] recorded a higher yield of wheat (Triticum aestivum L.), maize (Zea mays L.), millet (Pennisetum glaucum L.), apples (Malus domestica), and rapeseed (Brassica napus L.) when irrigated with TWW.…”
Section: Discussionmentioning
confidence: 99%